Mechanical damage caused by fruit-to-fruit impact of litchis. Issue 17 (2018) - Wang, Weizu; Yang, Zhou; Lu, Huazhong; Fu, Han
Abstract: Mechanical damage of litchi fruits caused by impact is a major problem for mechanical harvesting. During a shaking harvesting process, the impact between fruits is almost inevitable. Thus, it is necessary to study the characteristics of fruit-to-fruit impact of litchis. Impact tests were conducted between an upper specimen and a lower specimen on an impact device with Yuhebao and Guiwei variety of litchis. The modulus of elasticity of fruits after impact was measured with a tester to determine the damage of the fruits. Three impact times and four impact speeds were used in the tests. The results show that with impact speed = 2.8 m/s, 15-times impact caused significant damage to the fruits, while 5-times may only cause slightly damage. When the impact speed decreased to 0.98 m/s, no significant damage was observed after 15-times impact for Yuhebao litchis. Therefore, increase impact times or impact speed may cause more damage to the fruits. However, when the impact times or the impact speed were lower enough, damage may be very slight or even not happen.